Manajemen Airway Dikombinasi dengan Hand Held Fan dan Deep Breathing Exercise terhadap Penurunan Sesak Nafas pada Pasien Efusi Pleura Bilateral - Asilah Afnani Bisri; Haeril Amir; Rahmat Hidayat (Rumah Sakit Ibnu Sina, Makassar, 2025)
Pneumonia with bilateral pleural effusion may cause dyspnea due to reduced lung expansion and increased work of breathing. This case report describes clinical changes following an adjunct intervention package consisting of Airway management combined with a hand-held fan (HHF) and Deep breathing exercise (DBE) in the emergency department. A 35-year-old male presented with worsening dyspnea accompanied by chest pain and productive cough; baseline assessment showed a respiratory rate of 28 breaths/min and SpO₂ of 91%, and supplemental oxygen was administered as prescribed. The sequential intervention package (total 5 minutes) included Airway management (semi-Fowler positioning, breathing-control education, and effective coughing/huff cough), HHF directed to the face at a distance of approximately 15–20 cm for 2 minutes, and DBE for 5–10 repetitions (inhalation 2–3 s, hold 1–2 s, slow exhalation 4–6 s). Outcomes were assessed by comparing respiratory rate and SpO₂ at baseline and immediately after completing the package ( 1 minute after DBE), along with the patient’s subjective dyspnea report. The patient reported reduced dyspnea, with respiratory rate decreasing to 22 breaths/min and SpO₂ increasing to 96%. Conclusion: the Airway-management plus HHF and DBE package was followed by clinical improvement in this case; however, generalizability is limited by the single-case design without control, lack of stage-by-stage measurements, absence of a standardized dyspnea scale, and potential confounding from concurrent medical therapies.